U-1: ROLE OF DEENI MADARIS IN NATIONAL SOLIDARITY : قومی یکجہتی میں دینی مدارس کا کردار - Khan, Muhammad Iqbal; Khan, Hafiz Munir Ahmed; Mufti Imran-ul-Haq, (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
This paper is about the Promotion of solidarity and Peace activities regarding the role of Deeni Madaris. The purpose of this paper is to highlight the importance of peace and Unity for the development of the nation. In this context, the role of Deeni Madaris in promoting religious and peaceful activities can be neglected. Therefore, the role of Deeni Madaris and its teachers & llamas has a key position in formulating a united nation or a divided nation into different groups or different schools of thought. The purpose of this article is to pinpoint the shortcomings of our Madaris, to present the important role of Madaris in eliminating sectarianism and increasing unity among the nation so that followers of different schools of thought in Islam and followers of other religions could survive a peaceful and happy life. This thing will promote not only the economy but the society will go towards development and real progress. In this way, everyone will perform his worship activities according to his faith and religion without cursing and abusing the other. In short, this paper presents some key points to maintain in an Islamic Society which is essential to remove our sectarian differences and Conflicts. For this, we all will have to adopt and stress upon Semitic guidelines rather than adopting the Sayings and quotations of Scholars and imams of Jurisprudence only.